Minimization of Torque Ripples of Interior Permanent Magnet Synchronous Motors by Particle Swarm Optimization Technique - Aydin, Emrullah; Li, Yingjie; Aydin, Ilhan; Aydemir, M. Timur; Sarlioglu, Bulent (Ieee, 2015)
Permanent magnet synchronous motors are preferred for high-performance applications because of their high power density and efficiency. Particularly, interior permanent magnet (IPM) synchronous motors are typically used in electric or hybrid vehicles due to their high efficiency and field weakening capability. One of the most important design considerations for IPM machines is the torque ripple, which rises as a result of the interaction between the stator and rotor magnetomotive force fields. Torque ripple can cause unwanted vibrations and audible noise. The objective of this paper is to investigate the design of IPM machines to minimize torque ripple through optimization. Particle swarm optimization technique has been applied to analytical torque ripple equations to minimize the torque ripple. In the last section, finite element analysis (FEA) is implemented to verify the optimization results.
IEEE Transportation Electrification Conference and Exposition (ITEC) -- JUN 14-17, 2015 -- Dearborn, MI
Keywords: Particle swarm optimization; permanent magnet synchronous motors; torque ripple minimization